Magnetic-particle Based Signal Amplification Method Integrated with Mobile-devices for Low Cost Biosensing. (2017) - Mzava, Omary; Taş, Zehra; Lafcı, Vahit Can; Çakar, Mehmet Akif; Özdür, İbrahim and İçöz, Kutay
Abstract: We present a signal amplification method for biosensing applications using magnetic particles. In this method, mobile devices and simple spherical glass beads are used as a low-cost microscope to detect magnetic particles. Magnetic particles have two main functions; 1) conventionally capture, separate and transport target molecules 2) form magnetic dipoles under an applied external magnetic field to attract other magnetized particles. When magnetic particles accumulate and form a cluster, the corresponding pixel area in the image taken by the simple microscope is increased resulting in signal amplification. Current focus of new generation biosensor research is to increase the sensitivity levels of the devices to compete with current lab analysis tools while inherently having other advantages such as being low-cost, portable and simple. Biosensors based on micro/nano magnetic particles use various measurement techniques and amplification methods. In order to fully benefit from the advantages of micro/nano technology based systems, measurement set up must be also portable and have high sensitivity. Mobile devices and applications are taking place in medical fields and have high potential for future. In this work mobile devices are employed as measurement setups for the magnetic particle based sensing and signal amplification. The amplification method is not based on bimolecular binding thus cost efficient. After the images of the magnetic particles are taken, these images are sent to cloud computing for analysis by the mobile device. Matlab codes run on cloud servers for processing the images. Finally results are received and displayed on the mobile device. The mobile device based imaging system is able to detect 7 μm size particles within a 1500 μm x1500 μm area and magnetic bead accumulation resulted in at least 5-fold signal amplification. The applied magnetic field is approximately 15 mT and the cost of the system excluding mobile device is under 20 cents. The method is promising for immunomagnetic bead assisted biosensors.